The Effect of Perceptions, Knowledge of Taxation, and the Tax Volunteer Program on Accounting Students Career Interest in Taxation (Study on Accounting Students Participating in Tax Volunteers at Mataram University in 2024) - Komala, Ilhamni Intan; Nabila, D. Tialurra Della (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the impact of perceptions, taxation knowledge, and tax volunteer programs on accounting students' interest in a career in taxation. The research sample consisted of 33 students from Mataram University who had participated in the tax volunteer program. Data analysis using multiple linear regression revealed that perception and taxation knowledge did not significantly influence students' career interest, while the tax volunteer program had a positive and significant effect. Together, the three variables explained 28.1% of the variation in career interest, with the remaining influence coming from other factors. The study highlights the role of hands-on experience through the tax volunteer program in boosting students' interest in a taxation career. Future research is recommended to explore additional factors, such as intrinsic motivation and social support.